Mechanical Performance of Eco-Friendly Sandwich Wall with Rice Husk Recycled Concrete - Dingshi Chen; Maohua Du; Yubin Tian; Wenmiao Du (Advances in Civil Engineering)
In the construction industry, an approach to alleviate the environmental problem is to apply ecological composite materials to the construction field. In this paper, the authors added the recycled aggregate and the rice husks to the concrete and measured the strengths of rich husk recycled concrete (RHRC) with different factors as well as determined the constitutive model. Subsequently, the flexural experiment of RHRC sandwich wall was carried out and analyzed in detail, which proved that it could bear the wind loads in normal use condition by the calculation of the experimental data. Then, the compressive experiment and analyses were conducted similarly. Moreover, the finite element method was applied to study the influence of tie bars on the flexural bearing capacity and to deduce the simplified calculation method of vertical bearing capacity of RHRC walls.